Y Chromosomal Microdeletion; SY127 Gene Related Male Infertility Screening in Iraq - Zuhiaer, Mohammed; A. Kadhim, Raad; H. Al-Marzoqi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
SY127 is one of the main genes in the AZFb region that is located on the long arm of the human Y chromosome and has an essential role in fertility because deletions of the AZFb region cause the stopping of spermatogenesis.Materials & Methods: Subjects and semen analysis: In this study, 126 infertile males were analyzed who were diagnosed and treated at the Department of Al-Hillah Educational Hospital in Babil, Iraq, from September 2019 to January 2020. The DNA was extracted using DNA extraction kits (Invitrogen, USA). Then DNA amplification by multiplex PCR was performed using STS primers for the AZFb sub-region (SY127).Results: In this study, the SY127 gene was found in 73 (48.3%) cases out of 151 samples that were detected by the polymerase chain reaction (PCR) technique. It's revealed that microdeletions involving sY127 are significantly related to azoospermia. The high frequency of sY127 deletion, 9.59% (7/73), among azoospermic patients and the significant difference between the azoospermic group and the oligozoospermic group in the deletion of sY127 may indicate that microdeletions involving sY127 may be associated with severe spermatogenic failure. The present study concluded that microdeletions involving sY127 are related to azoospermia. Deletions of sY127, as well as deletions of sY84 or sY86 alone, may be a high risk factor for azoospermia. Conclusion: The SY127 gene was found in a higher percentage among oligoasthenozoospermia and asthenozoospermia than other cases involved in this study.